Hatchet - Paulsen, Gary. (New York : Puffin, 1988)
After a plane crash, thirteen-year-old Brian spends fifty-four days in the wilderness, learning to survive with only the aid of a hatchet given him by his mother, and learning also to survive his parents' divorce.
Wilson's Senior High School, January 1992.
Wilson's Junior High School, March 2008.
Notable/Best Books (A.L.A.), March 2008.
Book Links (A.L.A.), May 1995.
Child Study Children's Book Committee, September 2008.
Publisher's Weekly, September 2008.
Keywords: Survival -- Fiction; Divorce -- Fiction; Wilderness survival -- Fiction; Children of divorced parents -- Fiction; Action and adventure fiction